2012
DOI: 10.1007/s00117-011-2284-x
|View full text |Cite
|
Sign up to set email alerts
|

Stellenwert der PET/CT zur Bildgebung des kolorektalen Karzinoms

Abstract: To optimally exploit the synergy between morphologic and functional information, FDG-PET should generally be performed as an integrated FDG-PET/CT with a contrast-enhanced CT component in colorectal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…The role of PET/CT in radiotherapy planning and response monitoring is under evaluation. Meinel FG et al in their report have recommended a targeted use of PET-CT in cases of unclear M staging, prior to metastasectomy and in suspected cases of residual or recurrent colorectal carcinoma with equivocal conventional imaging (16). Several studies reported that FDG PET is superior to CT in assessing disease with a sensitivity of 84-100% and a specificity of 80-100% in the detection of local recurrence and the accuracy ranges from 74% to 96% (17,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The role of PET/CT in radiotherapy planning and response monitoring is under evaluation. Meinel FG et al in their report have recommended a targeted use of PET-CT in cases of unclear M staging, prior to metastasectomy and in suspected cases of residual or recurrent colorectal carcinoma with equivocal conventional imaging (16). Several studies reported that FDG PET is superior to CT in assessing disease with a sensitivity of 84-100% and a specificity of 80-100% in the detection of local recurrence and the accuracy ranges from 74% to 96% (17,18,19).…”
Section: Discussionmentioning
confidence: 99%